An analysis of loanwords in selected isiXhosa texts - Futuse,Liziwe (African Languages and Literatures, 2025)
Loanwords are well researched in many of the world's languages, but there is a dearth of research into their occurrence and significance in isiXhosa. Previous research on isiXhosa borrowed words concentrates on contemporary speech, but this study focuses on written texts, drawing on sources from the 1800s to the present time. The words in this corpus are analysed in terms of their domains (including religion, politics, and lifestyle) in order to establish what prompted the borrowing. The preoccupations, political tensions, practicalities, motivations of prestige and novelties involved in isiXhosa contact with missionaries and settlers dominate the corpus domains, and this allows for an argument that places historical events as a key motivator for lexical innovation. It is clear from the corpus that while Afrikaans was the source language for many of the early borrowings, these were soon overtaken by English loanwords, while words from other indigenous languages hardly feature. This finding could support the argument that South Africa's Bantu languages were originally one language, and thus shared a common lexicon. In line with research findings on loanwords in other languages, I established that nouns made up the majority of borrowed words. This study provides the first extensive treatment of phonological equivalences in loanwords between the language pairs of Afrikaans and isiXhosa and English and isiXhosa. The changing phonetics of loanwords, as represented in the different orthographic representations, suggests subtle changes in their isiXhosa pronunciation: early writers assiduously adapted the borrowed words to the phonology of isiXhosa, which is evident in how they are spelled, while contemporary writers increasingly spell the borrowed words as written in the source language. It is instructive that the paucity of loanwords in the domain of nature would suggest that there is nothing in their natural universe that isiXhosa-speakers had not already discovered, identified and named long before they made contact with missionaries and settlers. Finally, the fact that today's isiXhosa-speakers might be borrowing more words from English does not mean that the language is getting weaker, but rather that its speakers are expanding their linguistic repertoires to encompass subtle differences in meaning